Is there a Conflict of Interest in Indonesia’s SOE Investment Decision? - Daniel, Echo; Dalimunthe, Zuliani (Universitas Muhammadiyah Jakarta, 2024)
In financial management, the Director of State-Owned Enterprises (SOEs) in Indonesia synergizes with the Ministry of SOE to make investment decisions. One of the most common types of investment in SOEs is the purchase of shares in private companies. Through buying shares, SOEs can expand their business lines and project bigger profits. However, it is often found that the decision to purchase private company shares is made by SOEs due to a conflict of interest. This paper aims to determine the level of involvement of conflicts of interest in the decisions of SOEs in Indonesia to invest in the purchase of shares of private companies. Due to data limitations, the authors used a qualitative technique with an explanatory case study to meet the research aims. The analysis tested of 14 Indonesian SOEs' investment decisions when investing in the purchase of shares in private companies during the 2013–2022 period. The findings show allegations of conflicts of interest in several share investment decisions made by SOEs in Indonesia. This conflict of interest can occur because of a family relationship between the Board of Directors of SOEs and the management of private companies. In addition, there is also a political-party relationship between the parties involved. These findings can help several parties, including SOE and the Ministry of SOE, better understand the limits of investment that can be made. In the long run, the Ministry of SOE, as the supervisor of SOEs, can establish an early warning system to determine whether or not the investments made are appropriate. Most of the previous research only examined the effects of a company's investment and its impacts. It explores the company's stock price valuation process. No research has been found that specifically discusses SOE investment in Indonesia in private company shares.